Pengaruh Gaya Kepemimpinan, Motivasi Kerja Dan Reward Terhadap Kinerja Karyawan Departemen Main Production di PT. Samsung Electronics Indonesia - Novita Sari; Halipi Hazizan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Companies that want to develop and adapt to times must improve the quality of human resources in it. Improving the quality of human resources in the company will make employees carry out work in a professional, responsible and good attitude and can help companies meet increasingly complex market demands in the era of globalization. This study aims to determine the effect of leadership style, work motivation, and rewards on the performance of employees in the main production department at PT. Samsung Electronics Indonesia, either partially or simultaneously. This research is a quantitative study and the analytical tools in this study use the SPSS version 24 application with instrument test results in the form of validity tests, reliability tests, analytical methods using multiple linear regression analysis tests, classical assumption tests (normality test, multicollinearity test, heteroscedasticity test), hypothesis testing (t test and f test) and test the coefficient of determination. With a population of 340 and the sample technique used in this study is random sampling so that the total sample is 77 respondents based on the calculation of the slovin formula. The results of the calculation obtained t test of leadership style on performance obtained t count results greater than t Tabel (-4.302>-1.669), work motivation t test on performance obtained t count greater than t Tabel (4.936> 1.669) and reward t the performance test obtained by t count is greater than t Tabel (4.161> 1.669) and the results of the f test obtained the value of f count is greater than f Tabel (27.334). Referring to the test results, it can be concluded that leadership style, work motivation and rewards have a significant effect on employee performance both partially and simultaneously. In addition, it is also known based on testing that simultaneously leadership style, work motivation and rewards affect performance by 51%.